MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN ADMINISTRASI DI MADRASAH TSANAWIYAH NEGERI 2 BATANG HARI - Sukatin Sukatin; Fitri Nasution; Ine Damayanti (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
Human Resource Management Strategy in Improving Administration at Madrasah Tsanawiyah Negeri 2 Batang Hari, namely by planning, organizing, supervising and assessing, guided by the established curriculum. This study aims to determine how the strategy of human resource management in improving administration, especially in the implementation of learning. The method used in this study is a descriptive method with a qualitative approach. Data collection techniques in this study were carried out directly through interviews, observation and documentation studies. The subjects of this study were principals, vice principals for curriculum and teachers at MTs Negeri 2 Batang Hari. The research results obtained are: (1) the principal of the madrasa fosters teachers in the process of compiling learning programs such as lesson plans, annual programs, semester programs, and details of the effective week. (2) the head of the madrasah fosters teachers in the implementation of learning which is done by explaining the material, learning media, learning methods and learning resources. (3) the head of madrasah fosters professional improvement of teachers by means of supervision, upgrading, seminars and activating the MGMP as well as providing learning facilities and media.